Ненормативные этнонимы: проблема словарного описания - Krysin, Leonid (Wiener Slawistischer Almanach, 2023)
The article considers various types of non-standard ethnonyms in modern Russian and their lexicographic description in explanatory dictionaries of everyday speech. The term “substandard” is widely understood as comprising everything that contradicts a literary norm. Such an approach has made it possible to define ethnonyms as substandard. The need for a dictionary registration of such words is demonstrated. The system of their lexicographic description is illustrated by the examples of a number of entries and is shown to feature 11 “zones,” each of which contains a certain type of linguistically essential information regarding the word. This may serve as a good example of the structure of an entry.